A new species of Alopoglossus lizard (Squamata, Alopoglossidae) from the Southern Guiana Shield, northeastern Amazonia, with remarks on diagnostic characters to the genus - Ribeiro-Júnior, Marco Antônio (Zootaxa, 2018)
I describe a new species of Alopoglossus from the Southern Guiana Shield in northern Brazilian Amazonia. The new species morphologically resembles A. angulatus in having scales on sides of neck similar in shape to dorsals, nongranular, keeled, and imbricate. Nonetheless, the presence of four pairs of chin shields, with the third pair heptagonal and separated from gulars by large scales, can distinguish the new species from A. angulatus. This description increases the species diversity of the genus Alopoglossus in eastern Amazonia, from where only one taxon was recognized to occur. In addition, I discuss the nomenclature of some diagnostic characters, on the chin region, to the genus, and I present an updated key to Alopoglossus.